On the growth of the spectral measure - A. Boumenir (International Journal of Mathematics and Mathematical Sciences)
We are concerned with the asymptotics of the spectral measure associated with a self-adjoint operator. By using comparison techniques we shall show that the eigenfunctionals of L2 are close to the eigenfunctionals L1 if and only if dΓ1≈dΓ2 as λ→∞.